Mechanisms of action of the BCL-2 inhibitor venetoclax in multiple myeloma: a literature review - Cao, Qiang; Wu, Xinyan; Zhang, Qi; Gong, Junling; Chen, Yuquan; You, Yanwei; Shen, Jun; Qiang, Yi; Cao, Guangzhu (Frontiers in Pharmacology, 2023)
Abnormal cellular apoptosis plays a pivotal role in the pathogenesis of Multiple Myeloma (MM). Over the years, BCL-2, a crucial anti-apoptotic protein, has garnered significant attention in MM therapeutic research. Venetoclax (VTC), a small-molecule targeted agent, effectively inhibits BCL-2, promoting the programmed death of cancerous cells. While VTC has been employed to treat various hematological malignancies, its particular efficacy in MM has showcased its potential for broader clinical applications. In this review, we delve into the intricacies of how VTC modulates apoptosis in MM cells by targeting BCL-2 and the overarching influence of the BCL-2 protein family in MM apoptosis regulation. Our findings highlight the nuanced interplay between VTC, BCL-2, and MM, offering insights that may pave the way for optimizing therapeutic strategies. Through this comprehensive analysis, we aim to lay a solid groundwork for future explorations into VTC's clinical applications and the profound effects of BCL-2 on cellular apoptosis.